Evaluación de enmiendas orgánicas en la respuesta productiva del cultivo de tomate riñón (Solanum lycopersicum) variedad (Pietro) - Benalcazar Andrade, Stalyn Santiago (2022)
Agricultural soils are increasingly deteriorating and, as a result, their productivity is decreasing. The main causes of this problem are the massive use of mineral fertilizers and phytosanitary products, which generates a medium and long-term dependence that in turn causes soil deterioration and negative impacts on the ecosystem. An alternative to the present problem is the incorporation of organic amendments with a vision aimed at complementing the mineral fertilizers applied and thus achieving the desired productivity without affecting production costs. The main objective of this research was to evaluate the effect of organic amendments on the growth, development, and productivity of kidney tomato (Solanum Lycopersicum) of the variety (Pietro), in the canton of Ibarra, Imbabura Province. A Completely Randomized Block Design was implemented with four treatments, three types of organic amendments (lagoon sediments, ovine, vermicompost), and a control, with a dosage of 50 t ha-1. The results obtained indicated benefits in the morpho-physiological variable (days to flowering), obtaining a value of 29.33 days with the incorporation of lagoon sediments compared to the rest of the amendments used, as well as positive productivity results in the variables (number of fruits per bunch with a value of 5.60 fruits\; fruit size resulting in 8.94 cm\; yield per plant obtaining 0.51 kg ha-1 and yield per hectare with a value of 121390.31 kg ha-1). This shows that the use of organic amendments as a complement to fertilization is an efficient alternative to meet the needs of the crop and achieve the expected yields.